Impaired exercise performance in the heat is associated with an anticipatory reduction in skeletal muscle recruitment - Tucker, R.; Rauch, L.; Harley, Y.; Noakes, T. D. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
It has been found that exercise in the heat causes "central fatigue", in which an elevated body temperature (> 40°C) causes reduced central activation in the exercised muscles, leading to a lower force production during isometric contractions (Nybo and Nielsen, 2001). An alternative hypothesis suggests that impaired performance occurs due to an anticipatory exercise response which would "control the exercise work rate by regulating the number of motor units that are recruited or derecruited during prolonged exercise in the heat" (Marino et al., 2003). The aim of this study was to examine whether centrally regulated skeletal muscle recruitment was altered during dynamic exercise in hot (35°C) compared to cool (15°C) environments. Methods We submitted a group of well-trained male cyclists (n = 10) to two self-paced 20-km cycling time-trials, one at 35°C (HOT condition) and one at 15°C (COOL condition). Power output, integrated electromyographic activity (iEMG) of the quadriceps muscle, rectal and skin temperatures, heart rate and rating of perceived exertion (RPE) were measured throughout the trial. Data were analyzed using a two-way ANOVA for repeated measures. Where a significant effect was detected, post-hoc comparisons were made with a Tukey`s HSD for pairwise comparisons. significance was set at P<0.05. Results Rectal temperatures rose significantly during trials, but were not different between conditions until the 20th kilometer of the trials. Power output and iEMG activity of the quadriceps muscle decreased early in the HOT trial, when rectal temperatures, heart rates and RPE were similar between conditions. iEMG activity was significantly lower in HOT than in COOL at 10 and 20 km (Fig. 1), while power output was significantly reduced from 80% to 100% of the trial duration in the HOT compared to COOL condition (Fig 2). Discussion/Conclusion The reductions in power output and iEMG activity in advance of abnormal increases in rectal temperature, heart rate or perception of effort suggest the existence of a centrally controlled neural mechanism, which anticipates an abnormal elevation in body temperature, and alters skeletal muscle recruitment to allow completion of the exercise bout whilst thermal homeostasis is maintained. Impaired exercise performance in the heat is thus not the result of a miting core temperature, but occurs as part of the central regulation of skeletal muscle recruitment.